Genome-wide excision repair in Arabidopsis is coupled to transcription and reflects circadian gene expression patterns - Onur Oztas (Nature Portfolio, 2018)
Plants use nucleotide excision repair to maintain genome integrity in response to damage caused by stresses such as UV radiation. Here Oztas et al. use genome-wide profiling to show that excision repair in Arabidopsis is strongly coupled to transcription and reflects circadian patterns of gene expression.